Microbiological Quality of Laboratories Works - BABA-MOUSSA, FARID A. KADER SAÏD; BABA-MOUSSA, LAMINE SAÏD; AHOUANDJINOU, H.; DOUGNON, T. VICTORIEN (My University, 2016)
Hygiene and sanitation in laboratories are some important focus for the well-being of scientists and workers. Due to the lack of these notions, a new sanitation system named Polti Sani System has been tested to overcome the limitations of traditional methods. For this work, some American Type Culture Collection and Institute Pasteur of Strasbourg reference strains have been used. The biocides activities of the Sani System were assessed by the count of the total aerobic mesophilic bacteria in the working environment before and after disinfection. The Adenosine Triphosphate was also quantified. After a time contact of 30 seconds, Sani System reduced more than five logarithmic levels, the bacterial rate tested. The log reduction achieved with the fungi in the same conditions were greater than four logarithmic levels. The antimicrobial activity was observed both in the environment and on inert supports made of glasses, Plexiglas or tiles with an average reduction rate of 99.13%. This study showed that the Sani System associated with ATP-metry can be successfully used to quickly check the hygiene standards on surfaces or lab environment. It is a real challenge in terms of quality, efficiency and safety for the laboratories.
Keywords: Laboratory safety; sanitation system; saturated steam.